Analysis of ai-driven approaches to professional selfdetermination: a focus on psychology, skills, and market trends - Zhaxygeldiyeva, K. (Харківський національний автомобільно-дорожній універститет, 2024)
Artificial Intelligence (AI) is increasingly transforming career guidance by offering personalized recommendations based on psychological profiles, skill mapping, and labor market trends. This paper examines the current and potential applications of AI in career development, particularly in the fields of psychology, skill mapping, and market trend analysis. By leveraging AI-driven tools, career counselors can provide personalized advice by assessing individual personality traits, cognitive abilities, and professional skills. Additionally, AI systems use real-time labor market data to align individual capabilities with emerging job opportunities, helping people navigate an ever-evolving workforce landscape. This study also explores AI’s integration into career counseling tools, such as chatbots, and its role in skill mapping to match personal abilities with career demands. A systematic literature review (SLR) was conducted, including primary studies retrieved from databases such as ScienceDirect, IEEE Xplore, ResearchGate, and ASICT. The findings highlight the growing role of AI in shaping career decisions, offering new opportunities for career development in a competitive job market. Despite being in early stages, AI's potential for revolutionizing career guidance is significant, with the promise of improving decision-making accuracy and aligning skills with market needs.
Keywords: artificial intelligence; career counseling; professional self-determination; psychological self-assessment; personalized career guidance; career development